Sugar taxation policy and sugar consumption in Malaysia - Nivakan, Sritharan; Salawati, Sahari; Sharon Cheuk, Choy Sheung; Mohamed Ahmad, Syubaili (Rynnye Lyan Resources, 2024)
Malaysia has been taking initiatives to combat obesity as well as non-communicable diseases. A sugar-sweetened beverage (SSBs) tax was proposed in 2014 and implemented in 2019 with an excise duty of RM0.40 per litre for ready-to-drink sugar content. This article aimed to spark a discussion about Malaysia's current sugar tax policies to reduce excessive sugar consumption among Malaysians. However, the alarming rise in the number of obesity and diet-related noncommunicable diseases indicates that the sugar tax control measures are less effective in combating health issues. This study compares Malaysia's neighbours' sugar tax policies and other sugar consumption-related measures. To combat the emerging sugar-related health issues in Malaysia, the government should collaborate with food manufacturers to reduce the amount of sugar in their food production, abate sugar-containing products’ promotion, educate the consequences of excess sugar consumption at all levels of education, apply sugar taxes with lower tax base rate and specific tax rate depends on sugar addition, and form a regional policy between neighbours.